Non-RhD alloimmunization in pregnancy: an updated review - Sabrina Menes Ares; Luciano Marcondes Machado Nardozza; Edward Araujo Júnior; Eduardo Félix Martins Santana (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2024)
Abstract RhD alloimmunization in pregnancy is still the main cause of hemolytic disease of the fetus and neonate (HDFN). Nevertheless, there are other antigens that may be associated with the occurrence of this phenomenon and that have been growing in proportion, given that current prevention strategies focus only on anti-RhD antibodies. Although not widespread, the screening and diagnostic management of the disease caused by these antibodies has recommendations in the literature. For this reason, the following review was carried out with the objective of listing the main red blood cell antigen groups described - such as Rh, ABO, Kell, MNS, Duffy, Kidd, among others - addressing the clinical importance of each one, prevalence in different countries, and recommended management when detecting such antibodies during pregnancy.